Diversity Of Terrestrial Microalgae (Including Lichen Photobionts) Along An Altitudinal Gradient In A Tropical Mountain Forest (Ecuador) - Beck, A. (2017)
DIVERSITY OF TERRESTRIAL MICROALGAE (INCLUDING LICHEN PHOTOBIONTS) ALONG AN ALTITUDINAL GRADIENT IN A TROPICAL MOUNTAIN FOREST (ECUADOR)